2023
DOI: 10.1002/bse.3360
|View full text |Cite
|
Sign up to set email alerts
|

What motivates the purchasing of green apparel products? A systematic review and future research agenda

Abstract: The contemporary business landscape is witnessing an ever‐increasing concern for environmental sustainability, which has also surfaced in the apparel industry through the introduction of green apparel. Whether the adoption of green apparel is as a result of growing external pressures on firms to adopt green practices or due to deliberate strategies to incorporate sustainable orientation in the making of products, it remains a topical subject—making a comprehensive account of the existing academic literature in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 130 publications
0
11
0
Order By: Relevance
“…(2021) reported that some factors have been shown to affect the beer choices such as price, brand, distribution, differentiation and packaging, contributing to consumer choice. A significant body of knowledge is now emerging, which investigates the role of consumer characteristics, patronage and other behavioral actions (Arum et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2021) reported that some factors have been shown to affect the beer choices such as price, brand, distribution, differentiation and packaging, contributing to consumer choice. A significant body of knowledge is now emerging, which investigates the role of consumer characteristics, patronage and other behavioral actions (Arum et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Food tourism is derived from tourists’ interest in exploring food and drinks around the host destination (Tung and Ritchie, 2011). Plentiful studies have stated that food is critical in outlining a particular destination’s uniqueness (Schwartz, 2020; Kaur et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…, 2021). Other studies as Arun et al. (2021) highlight the importance of carrying out innovative activities in the gastronomic tourism sector, pointing out the key importance of green restaurants in creating a unique and innovative gastronomic experience.…”
Section: Literature Reviewmentioning
confidence: 99%